Proceso de atención de enfermería en el adulto mayor con diabetes mellitus y complicaciones circulatorias. - Ula Montes, Lizbeth Carolina (2023)
Diabetes mellitus is a metabolic disorder with extensive etiologies characterized by chronically increased blood glucose levels with alterations in the metabolism of carbohydrates, proteins, and fats caused by insulin secretion and action. In Ecuador, there has been a significant increase in mortality in the last century as a result of type II diabetes mellitus, with a total of 4,895 deaths. A nursing care process was applied to a 68-year-old male patient with a characteristic symptomatic picture of the disease through physical examination, his symptoms characterized by holocranial headache of moderate intensity, polydipsia accompanied by asthenia, polyphagia, tinnitus and dizziness, in addition, through the Marjorie Gordon model, the affected functional patterns were evidenced, which allowed the identification of the patient's health needs. To carry out the diagnoses, interventions and results, the NANDA, NIC and NOC taxonomies were applied, which allowed improving care and improving the quality of life of the patient during their hospital stay.